The African Union Ten Years After : Solving African Problems with Pan-Africanism and the African Renaissance. - Muchie, Mammo (Africa Institute of South Africa, 2013)
This book looks at the first ten years of the African Union. This is the second in a series of books that will be produced each year from annual conferences held on the multi-faceted issue of African liberation. The key themes of the book explore ways of improving the effectiveness of the African Union, fostering unity amongst African countries through entrenchment of pan-Africanism, and building ownership of the African Union by the African people and their communities. In addition, the thoughts of key figures of pan-Africanism and black emancipation, such as Sylvester Williams and Frantz Fan.